Regulation of major histocompatibility complex class II gene expression, genetic variation and disease. - Handunnetthi, L; Ramagopalan, S; Ebers, G; Knight, J (2010)
Major histocompatibility complex (MHC) class II molecules are central to adaptive immune responses and maintenance of self-tolerance. Since the early 1970s, the MHC class II region at chromosome 6p21 has been shown to be associated with a remarkable number of autoimmune, inflammatory and infectious diseases. Given that a full explanation for most MHC class II disease associations has not been reached through analysis of structural variation alone, in this review we examine the role of genetic variation in modulating gene expression. We describe the intricate architecture of the MHC class II regulatory system, indicating how its unique characteristics may relate to observed associations with disease. There is evidence that haplotype-specific variation involving proximal promoter sequences can alter the level of gene expression, potentially modifying the emergence and expression of key phenotypic traits. Although much emphasis has been placed on cis-regulatory elements, we also examine the role of more distant enhancer elements together with the evidence of dynamic inter- and intra-chromosomal interactions and epigenetic processes. The role of genetic variation in such mechanisms may hold profound implications for susceptibility to common disease.